Tandem mass tag-based quantitative proteomics analysis reveals the effects of the α-lactalbumin peptides GINY and DQW on lipid deposition and oxidative stress in HepG2 cells - Haoran Chen; Xiaofen Qi; Kaifang Guan; Rongchun Wang; Qiming Li; Ying Ma (Journal of Dairy Science, 2023)
ABSTRACT: The objective of this study was to investigate the mechanism by which the α-lactalbumin peptides Gly-Ile-Asn-Tyr (GINY) and Asp-Gln-Trp (DQW) ameliorate free fatty acid–induced lipid deposition in HepG2 cells. The results show that GINY and DQW reduced triglyceride, total cholesterol, and free fatty acid levels significantly in free fatty acid–treated HepG2 cells. Based on proteomic analysis, GINY and DQW alleviated lipid deposition and oxidative stress mainly through the peroxisome proliferator-activated receptor (PPAR) pathway, fatty acid metabolism, oxidative phosphorylation, and response to oxidative stress. In vitro experiments confirmed that GINY and DQW upregulated the mRNA and protein expression of fatty acid β-oxidation–related and oxidative stress–related genes, and downregulated the mRNA and protein expression of lipogenesis-related genes by activating peroxisome proliferator-activated receptor α (PPARα). Meanwhile, GINY and DQW reduced free fatty acid–induced lipid droplet accumulation and reactive oxygen species generation, and enhanced the mitochondrial membrane potential and ATP levels. Furthermore, GINY and DQW enhanced carnitine palmitoyl-transferase 1a (CPT-1a) and superoxide dismutase activities, and diminished acetyl-coenzyme A carboxylase 1 (ACC1) and fatty acid synthase (FASN) activities in a PPARα-dependent manner. Interestingly, GW6471 (a PPARα inhibitor) weakened the effects of GINY and DQW on the PPARα pathway. Hence, our findings suggest that GINY and DQW have the potential to alleviate nonalcoholic fatty liver disease by activating the PPARα pathway.